(untitled) (Qawanin Jurnal Ilmu Hukum, 2021)
In writing this scientific journal, the author discusses the problem of juridical review of land rights ownership of dowries in weddings in Belawa sub-district, Wajo regency, relanted to the giving of dowrie in marriage, this is based on the fact that Wajo district is a district if there is a problem with land ownership, giving a dowry in marriage, the problem is this is what the authors appointed to research the implementation of dowry granting in marriage according to national land law and legal protection for women who receive land given dowries in marriage in Belawa District, analyze the implementation of dowry in marriage according to national land law know and analyze.Analyzing legal protection for land rights owners who give dowry in weddings in Belawa Sub-district, Wajo Regency.